Future of the state – welfare state? Lithuania’s path - Taminskaitė, Gabrielė (Vilnius University Open Series, 2020)
This article analyses the rapport between the concepts of the welfare state and the social state. It also reveals the diversity of theoretical typologies of the welfare state and their significance in assessing the status of a country as a welfare state. By analysing the Lithuanian constitutional jurisprudence and legal doctrine, this article seeks to reveal Lithuania’s status as a welfare state, its origin and the connection with solidarity as an essential principle in the implementation of social rights nowadays and in the future.
Keywords: welfare state; principle of solidarity; constitutional principles